Extraction, isolation, characterization and antimicrobial activities of non-extractable polyphenols from pomegranate peel. (30th July 2021) - Sun, Shengwei; Huang, Siqi; Shi, Yaning; Shao, Yuting; Qiu, Jiarong; Sedjoah, Rita-Cindy Aye-Ayire; Yan, Zhenzhen; Ding, Liping; Zou, Dandan; Xin, Zhihong
Highlights: Three unique non-extractable polyphenols were identified by HRMS and LC-ESI-MS/MS. Four pentacyclic triterpenoids, one sterol and one sterol glycoside were isolated. Three pentacyclic triterpenoids were identified from pomegranate peel for the first time. Antibacterial activity might result from the collective effect of multiple compounds. Abstract: Non-extractable polyphenols (NEPPs) in pomegranate peel were released by acid hydrolysis followed by extraction using ethyl acetate (EtOAc). Ten NEPPs were identified in the hydrolysate using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS). Six compounds were then isolated from the EtOAc extracts whose structures were identified as β -sitosterol-3-O-glycoside (1 ), β -sitosterol (2 ), ursolic acid (3 ), corosolic acid (4 ), asiatic acid (5 ) and arjunolic acid (6 ) using a wide range of spectroscopic analyses. Compounds 4 –6 were isolated for the first time from pomegranate peel. Antimicrobial experiments revealed that compound 3 and 5 showed significant antimicrobial activity against a range of pathogens, particularly compound 5 which exhibited selective inhibitive activity towards Staphylococcus aureus with a minimum inhibitory concentration (MIC) of 16 μg/ml. The present study has provided new insights into the composition of bound chemicals in pomegranate peel and laid a foundation for improving its further processing and utilization.